2018
DOI: 10.1016/j.biopsycho.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Emotion lies in the eye of the listener: Emotional arousal to novel sounds is reflected in the sympathetic contribution to the pupil dilation response and the P3

Abstract: Novel sounds in the auditory oddball paradigm elicit a biphasic dilation of the pupil (PDR) and P3a as well as novelty P3 event-related potentials (ERPs). The biphasic PDR has been hypothesized to reflect the relaxation of the iris sphincter muscle due to parasympathetic inhibition and the constriction of the iris dilator muscle due to sympathetic activation. We measured the PDR and the P3 to neutral and to emotionally arousing negative novels in dark and moderate lighting conditions. By means of principal com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 48 publications
14
87
0
Order By: Relevance
“…Auditory pupil responses have previously been found to be larger for arousing than neutral sound stimuli (Partala & Surakka, ; Widmann, Schroger, & Wetzel, ). Interestingly, Widmann et al () found that the initial component of this auditory pupil response (within approximately 1 s after sound onset) was related solely to stimulus novelty and not to the arousing intensity of the presented sound material. However, in our case, the auditory pupil response was not elicited by emotionally arousing material but was triggered during the anticipation of a US (or safety for CS−).…”
Section: Discussionmentioning
confidence: 94%
“…Auditory pupil responses have previously been found to be larger for arousing than neutral sound stimuli (Partala & Surakka, ; Widmann, Schroger, & Wetzel, ). Interestingly, Widmann et al () found that the initial component of this auditory pupil response (within approximately 1 s after sound onset) was related solely to stimulus novelty and not to the arousing intensity of the presented sound material. However, in our case, the auditory pupil response was not elicited by emotionally arousing material but was triggered during the anticipation of a US (or safety for CS−).…”
Section: Discussionmentioning
confidence: 94%
“…First, we analyzed infants' pupil dilation, an indicator of both attention to a stimulus 57 and emotional arousal in response to it 58 , including during music listening 59,60 . If the lullabies relaxed infants, then pupil size should decrease during lullabies, relative to non-lullabies -contrasting sharply with an attention account for the heart rate findings, which would predict increases in pupil size.…”
Section: Exploratory Analysesmentioning
confidence: 99%
“…Accumulated evidence in humans and animals shows that pupil diameter may be a reliable marker of cognitive processing [36][37][38] . Increasing work also suggests that a temporal principal component analysis (PCA) can be used to decompose pupil measures into dissociable features that reflect distinct cognitive processes [39][40][41][42][43][44] . For instance, one recent study used PCA decomposition to show that a specific sub-component of pupil dilation is triggered just prior to the onset of memory retrieval decisions, suggesting that this response might signal the anticipation of an impending decision/response 40 .…”
mentioning
confidence: 99%